The scientific basis for the formation of spiritual and moral qualities in future educators - Jabbarova, Munira (The Lingua Spectrum, 2025)
The issue of spiritual and moral education is becoming one of the most important, pressing problems today. This article discusses the importance of the formation of spiritual and moral education in future educators and its pedagogical content, analysis in scientific, historical and literary sources.